Current and novel polymeric biomaterials for neural tissue engineering - Boni, Rossana (J Biomed Sci, 2018)
The nervous system is a crucial component of the body and damages to this system, either by of injury or disease, can result in serious or potentially lethal consequences. Restoring the damaged nervous system is a great challenge due to the complex physiology system and limited regenerative capacity. Polymers, either synthetic or natural in origin, have been extensively evaluated as a solution for restoring functions in damaged neural tissues. Polymers offer a wide range of versatility, in particular regarding shape and mechanical characteristics, and their biocompatibility is unmatched by other biomaterials, such as metals and ceramics. Several studies have shown that polymers can be shaped into suitable support structures, including nerve conduits, scaffolds, and electrospun matrices, capable of improving the regeneration of damaged neural tissues. In general, natural polymers offer the advantage of better biocompatibility and bioactivity, while synthetic or non-natural polymers have better mechanical properties and structural stability. Often, combinations of the two allow for the development of polymeric conduits able to mimic the native physiological environment of healthy neural tissues and, consequently, regulate cell behaviour and support the regeneration of injured nervous tissues. Currently, most of neural tissue engineering applications are in pre-clinical study, in particular for use in the central nervous system, however collagen polymer conduits aimed at regeneration of peripheral nerves have already been successfully tested in clinical trials. This review highlights different types of natural and synthetic polymers used in neural tissue engineering and their advantages and disadvantages for neural regeneration.